The Voices of the Youth: How Indigenous Young People Experience Plans of Care - Madigan, Brittany (2015)
Indigenous people in Canada have suffered through immense trauma since colonization, and child welfare agencies have contributed to the assimilation of Indigenous children. This research explores the stories of Indigenous people who have been in the care of Children’s Aid Society in Ontario and how they have experienced their plan of care. Every child in the child welfare system has a plan of care completed by their worker at regular intervals. This document is intended to review the child’s progress in various dimensions of their lives and facilitate goal-setting for the future. The plan of care is a standardized document that is created from a Western perspective and thus does not necessarily reflect Indigenous culture or the child’s true self. Using a mixed methods approach with a strong emphasis on Indigenous Methodologies, two Indigenous young adults shared their stories about their experiences with plans of care. In addition, an Indigenous key informant provided context from an Indigenous perspective on how plans of care can be improved for Indigenous children in care. To understand the plan of care document from a child/youth’s perspective, the author of this research asked a co-worker to complete a plan of care on their life. A critique of this experience is shared in this study. Findings suggest that experiences with plans of care can vary significantly, and depend greatly on the relationship between the young person and their child welfare worker. The two Indigenous young adults valued participation in their plan of care and found the goal setting to be useful when they were consulted. However, it is determined that the child welfare worker can bring Indigenous culture into the document in creative ways. These findings lead to recommendations for change at the micro and macro levels involving greater opportunities for relationship-building, space for young people to participate, and including Indigenous knowledge in child welfare practice. Thesis Master of Social Work (MSW)